Strong Circular Dichroism in Single Gyroid Optical Metamaterials. Issue 13 (7th May 2020) - Kilchoer, Cédric; Abdollahi, Narjes; Dolan, James A.; Abdelrahman, Doha; Saba, Matthias; Wiesner, Ulrich; Steiner, Ullrich; Gunkel, Ilja; Wilts, Bodo D.
Abstract: Over the past two decades, metamaterials have led to an increasing number of biosensing and nanophotonic applications due to the possibility of a careful control of light propagating through subwavelength features. Chiral nanostructures (characterized by the absence of any mirror symmetry), in particular, give rise to unique chiro‐optical properties such as circular dichroism and optical activity. Here, a gyroid optical metamaterial with a periodicity of 65 nm exhibiting a strong circular dichroism at visible wavelengths is presented. This bottom‐up approach, based on metallic replication of the gyroid morphology in triblock terpolymer films, generates a large area of periodic optical metamaterials. A strong circular dichroism in gold and silver gyroid metamaterials at visible wavelengths is observed. It is shown that the circular dichroism is inherently linked to the handedness of the gyroid nanostructure and its tuneability is demonstrated. The optical effects are discussed and compared to other existing systems, showing the potential of bottom‐up approaches for large‐scale circular filters and chiral sensing. Abstract : Chiral metamaterials offer a unique opportunity to control an optical response based on the handedness of the light; however, their fabrication is extremely challenging for visible wavelengths. Here, a strong and tunable circular dichroism is reported for metallic 3D gyroid metamaterials fabricated via a polymer‐based bottom‐up fabrication approach.